Creation and Evaluation of a Clinical Informatics Match: Initial Findings - Hron, Jonathan D.; Lehmann, Christoph U.; Long, S. Wesley; Pageler, Natalie M.; Kannry, Joseph; Levy, Bruce; Leu, Michael G. (Applied Clinical Informatics, 2023)
Background Clinical Informatics (CI) fellowship programs utilize the Electronic Residency Application Service (ERAS) to gather applications but until recently used an American Medical Informatics Association (AMIA) member-developed, simultaneous offer–acceptance process to match fellowship applicants to programs. In 2021, program directors collaborated with the AMIA to develop a new match to improve the process.Objective Describe the results of the first 2 years of the match and address opportunities for improvement.Methods We obtained applicant data for fellowship applicants in 2021 and 2022 from the ERAS and match data for the same years from the AMIA. We analyzed our data using descriptive statistics.Results There were 159 unique applicants over the 2-year period. Applicants submitted 2,178 applications with a median of 10 per applicant (interquartile range [IQR] 3–20). One hundred and four applicants (65.4%) participated in the match and ranked a median of seven programs (2–12). Forty-two programs in 2021 and 47 programs in 2022 offered a combined total 153 positions in the match. Participating programs ranked a median of eight applicants per year (IQR 5–11). Of participating applicants, 95 (91.3%) successfully matched and of those 66 (69.5%) received their top choice. Thirty-two programs (76.2%) matched at least one candidate in 2021 and 33 programs (70.2%) matched at least one candidate in 2022. In both years, 24 programs filled all available slots (57.1% in 2021 and 51.1% in 2022).Conclusion Applicants were extremely successful in the new match, which successfully addressed most of the challenges of the simultaneous offer–acceptance process identified by program directors. However, applicant attrition resulted in a quarter of programs going unmatched. Although many programs still filled slots outside the match, fellowship slots may remain unfilled while the CI practice pathway remains open.
Keywords: accreditation and licensure; clinical informatics; education; physician; workforce